Evaluating Sports Infrastructure Disparity: A Comparative Analysis of Football Extracurricular Facilities in Urban and Rural Areas - Ade Evriansyah Lubis; Tite Juliantine; Amung Ma’mun; Sucipto Sucipto (Journal Of Sport Education (JOPE), 2024)
The infrastructure disparity between urban and rural areas is a systemic issue in the development of sports talent in Indonesia. This article aims to analyze the gap in football extracurricular facilities through library research. Data were collected from national and international journal articles as well as other supporting documents (secondary data) over the past 10 years. The analysis results indicate that schools in urban areas tend to have access to better-equipped fields and more modern equipment, while schools in rural areas often face challenges such as non-standard fields and a lack of supporting equipment. The discussion highlights that this disparity impacts the national football achievement pyramid. Therefore, it can be concluded that a more inclusive infrastructure budget redistribution policy is needed to mitigate geographical disparities.